Optimization of High Frequency Welding Parameters of PVC Coating on Polyester Fabric - Khaothong, Kunthakorn; Priyadumkol, Jetsadaporn; Chaiworapuek, Weerachai; Kaisinburasak, Tinnasit (Trends in Sciences, 2022)
This study optimized welding parameters on polyester fabric coated with PVC by applying high frequency welding technique. Taguchi experimental design was adopted in this evaluation. Three levels of width of seam and time of high frequency welding were applied and analyzed with ANOVA statistical method with α = 0.05. The optimized result shows that the input parameters providing maximum failing load for welding in warp and weft directions are the following: Width of seam (27 mm) and time of welding (12 s). The maximum failing load were 87.8 and 75.8 N/mm for warp direction and weft direction, respectively, In addition, the statistic analytical result indicated that the width of seam was the most significant factor and the predicted optimal value of failing load were 88.5 and 80.5 N/mm for warp direction and weft direction, respectively, shows that the average percentage error is less than 2 % so that the forecast equation is appropriate for the explanation of the variables for this study and provide statistical reliability. The result was verified through confirmation experiments, the high frequency welding was suitable for welding PVC Coating on Polyester Fabric.